Effects of health at every size based interventions on health-related outcomes and body mass, in a short and a long term - Suárez, Rosario; Cucalon, Gabriela; Herrera, Carolina; Montalvan, Martha; Quiroz, Jestin; Moreno, Melissa; Sarmiento-Andrade, Yoredy; Cabañas-Alite, Luis (Frontiers in Nutrition, 2024)
Objective: This study aims to provide rapid and up-to-date evidence on the effectiveness of Health at Every Size (HAES) interventions compared to controls or other conventional approaches in individuals with overweight or obesity, with the goal of developing more effective and body-diverse respectful strategies. Methods: A review of literature was carried out using the following databases: PubMed, Scopus, Embase, Web of Science, and SciELO. Research articles were selected based on predefined inclusion and exclusion criteria. Extracted data included study characteristics (design, setting, population demographics, sample size, intervention characteristics, study duration, and follow-up period) and health-related outcomes. Results: The search yielded 324 articles, of which 20 articles met the inclusion and exclusion criteria. The majority of studies focused on lifestyle improvement, particularly in nutrition, body image, and relationships with food, utilizing a HAES approach. Additionally, other studies examined outcomes such as general well-being, body weight, body composition, cardiovascular risk, and changes in physical activity. Long-term results were particularly noted in studies incorporating physical activity interventions. Conclusion: HAES interventions appear to be a feasible strategy for promoting overall health and wellness, regardless of body size or shape. However, further evaluation is needed to assess the sustainability of these changes and their long-term impact, as current evidence suggesta they may not be maintained over time.